Effect of Size on Phase Mixing Patterns in Rapidly Solidified Au–Ge Nanoparticles - Olha Khshanovska; Vladyslav Ovsynskyi; Aleksandr Kryshtal (Nanomaterials, 2025)
We investigated the morphological patterns, crystalline structures and their thermal stability in solidified Au–Ge nanoparticles ranging in size from 10 to 500 nm. Liquid Au–Ge alloy nanoparticles with hypoeutectic composition were rapidly cooled from a temperature of 500 °C in a TEM and characterized using advanced TEM techniques. We demonstrated that Au–Ge nanoparticles 10–80 nm in size predominantly solidified into a Janus-like morphology with nearly pure single-crystalline hcp Au and diamond cubic Ge domains. These particles remained stable up to the eutectic temperature, indicating that Ge doping and particle size play key roles in stabilizing the hcp Au phase. In turn, larger nanoparticles exhibited a metastable core–shell morphology with polycrystalline Ge shell and hcp Au-Ge alloy core under solidification. It was shown that the mentioned morphology and crystalline structure evolved into the equilibrium Janus morphology with fcc Au and diamond Ge domains at temperatures above ≈160 °C.